2010
DOI: 10.1111/j.1755-3768.2009.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography is helpful in the diagnosis of foveal hypoplasia

Abstract: ABSTRACT.Purpose: To investigate whether optical coherence tomography (OCT) is helpful in the diagnosis of foveal hypoplasia in children. Methods: Children with albinism and aniridia were examined with Stratus OCT 3 software 4.0.1 (Carl Zeiss Meditec, Dublin, California, USA). A qualitative examination of the macular area was performed with a 128 A-scans ⁄ secondsingle-scan. Macular thickness was measured quantitatively with an automatic fast macular map protocol. The average thickness ⁄ volume of the macula w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 29 publications
3
43
1
1
Order By: Relevance
“…1,2 In the past decade, optical coherence tomography (OCT) has become the preferred methodology in the detection of foveal hypoplasia. 3 Foveal hypoplasia has been described to be associated with mutations in numerous genes causing a spectrum of ocular disorders. 2 PAX6 (MIM 607108) mutations have been shown to underlie isolated foveal hypoplasia, foveal hypoplasia and presenile cataract syndrome, as well as foveal hypoplasia with anterior segment anomalies (MIM 136520).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the past decade, optical coherence tomography (OCT) has become the preferred methodology in the detection of foveal hypoplasia. 3 Foveal hypoplasia has been described to be associated with mutations in numerous genes causing a spectrum of ocular disorders. 2 PAX6 (MIM 607108) mutations have been shown to underlie isolated foveal hypoplasia, foveal hypoplasia and presenile cataract syndrome, as well as foveal hypoplasia with anterior segment anomalies (MIM 136520).…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent studies have shown that OCT can be used as a diagnostic aid and prognostic indicator for the foveal hypoplasia. 4,10,11 In addition structural-functional correlation studies have been performed to document OCT findings in foveal hypoplasia although most of them were disease specific for albinism. Harvey et al showed a weak but significant correlation between macular thickness and visual acuity.…”
Section: Hhmi Author Manuscriptmentioning
confidence: 99%
“…12 In contrast, Holmstrom et al did not find significant correlation between central macular thickness and visual acuity (VA). 10 Seo et al proposed a grading system for foveal hypoplasia in albinism, this was based on: (1) foveal hyporeflectivity, (2) choroidal transillumination, (3) tram tract sign and (4) foveal depression. They showed in 13 patients that visual acuity correlates well with degree of foveal hypoplasia.…”
mentioning
confidence: 99%
“…Foveal hypoplasia refers to a condition in which the foveal depression is not formed and all neurosensory retinal layers are observed in the area presumed to represent the fovea [1][2][3][4]. Foveal hypoplasia is associated with aniridia, albinism, microphthalmus, achromatopsia, and retinopathy of prematurity; however, it may also occur in isolation [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Foveal hypoplasia is associated with aniridia, albinism, microphthalmus, achromatopsia, and retinopathy of prematurity; however, it may also occur in isolation [1][2][3]5,6]. Development of the foveal pit begins at fetal week 25, and is completed by the fourth year after birth [7].…”
Section: Introductionmentioning
confidence: 99%